Two‐dimensional magnetic transition metal chalcogenides. (4th May 2021) - Huang, Yu Li; Chen, Wei; Wee, Andrew T. S.
Abstract: The field of two‐dimensional (2D) magnets has expanded rapidly during the past several years since the first demonstration of intrinsic 2D magnetism in atomically thin CrI3 and Cr2 Ge2 Te6 in 2017. 2D transition metal chalcogenides (TMCs), a class of strongly correlated materials, have exhibited a wide variety of novel electronic and optical properties, and more recently magnetism. Here, we review recent experimental progress achieved in the growth of 2D magnetic TMC materials using chemical vapor deposition and molecular beam epitaxy methods. Outstanding examples include the demonstration of room temperature intrinsic and extrinsic ferromagnetism in monolayer VSe2, MnSe2, Cr3 Te4, V‐doped WSe2, and so on. A brief discussion on the origin of the exotic magnetic properties and emergent phenomena is also presented. Finally, we summarize the remaining challenges and future perspective on the development of 2D magnetic materials for next‐generation spintronic devices. Abstract : The realization of long‐range magnetic ordering in the two‐dimensional (2D) limit opens up opportunities to explore 2D magnetic states and potential applications in 2D spintronics. Here, we review recent experimental progress achieved in the 2D transition metal chalcogenides with intrinsic and extrinsic magnetism.